Teorija uma, izvršilne funkcije in metajezikovne zmožnosti pri osebah z motnjami avtističnega spektra - Hacin Beyazoglu, Kaja (Anthropos (Ljubljana), 2021)
Autism spectrum disorders (ASD) are a neurobiological disorder characterized by persistent deficits in social interactions, social communication, and behaviour. These deficits have been the subject of a great deal of past psychological research offering new knowledge and insight into the problems of people with ASD. In this review article, we present the findings of research on the deficits of people with ASD in terms of theory of mind and executive functions – two areas where people with ASD often show the most problems in everyday life – and metalinguistic competences. Metalinguistic competences are less frequently studied than theory of mind and executive functions, although they are closely related to them. It has become clear from the results of various studies that not all of the problems of people with ASD can be explained by domain-specific deficits or individual processes. Therefore, this article addresses the relationship between these cognitive abilities and processes, and the specifics of this relationship in people with ASD. For future research, questions arise about various dynamic interactions between cognitive abilities and processes, developmental pathways of individual abilities and mechanisms used by people with ASD in everyday life.
Keywords: autism spectrum disorders; executive function; izvršilne funkcije; metajezikovno zavedanje; metalinguistic awareness; motnje avtističnega spektra; pripovedovanje zgodb; psihologija; psychology; storytelling; teorija uma; theory of mind